The potential of employing a novel hybrid solar chimney power plant in the Arabian Gulf: A case study - Abdelsalam, Emad (2023)
Many countries worldwide are setting energy strategies to meet the future NetZero goal, including the states in the Arabian Gulf. Hence, this work assesses deploying a hybrid solar chimney power plant (HSCPP) in the Arabian Gulf countries to meet this goal. The proposed HSCPP not only produces clean energy but also produces distilled water and reduces CO2 emissions to the atmosphere. Hourly actual weather conditions (solar irradiation, temperature, wind speed, and meteorological factors) for one full year were incorporated with the HSCPP mathematical simulation to evaluate its performance in fourteen locations (Bahrain, Iraq, Kuwait, Oman, Qatar, UAE, Saudi Arabia, and Yemen), spanning the entire Arabian Gulf. The results showed varying HSCPP performance regarding electricity and water production, depending on the geographical and meteorological conditions. Shahrua City in the Kingdom of Saudia Arabia showed the highest electricity production and CO2 emissions reduction. Conversely, Sanaa in Yamen showed the most minor electricity production and the least CO2 emission reduction. Furthermore, Jal Aliyah produced the freshest water in Kuwait, while Sanaa had the least. This study showed that the HSCPP can meet the Arabian Gulf region's power and water demand while lowering carbon emissions.